The Empire Within: Postcolonial Thought and Political Activism in Sixties Montreal - Mills, Sean (McGill-Queen's University Press, 2010)
Keywords: Groupes populaires; Idéologies

Quebec, Haiti, and the Deportation Crisis of 1974 - Mills, Sean (Canadian Historical Review, 2013)
Keywords: Haïtiens

French Canadians and the Beginning of the War of 1812: Revisiting the Lachine Riot - Mills, Sean (Histoire sociale / Social History, 2005)
Historians have generally claimed that, during the War of 1812, unlike in earlier periods, French Canadians eagerly rallied to the British cause and willingly fought to defend British North America from American invasion. Nearly all studies of French-Canadian participation in the war, however, focus on the Battle of Châteauguay in 1813, and few examine the first year of the war. A close look at French Canadians’ reactions to the outbreak of the War of 1812 would indicate that they were hardly unanimous in their support. A detailed study of the largest and most violent act of resistance — a riot that broke out at Lachine at the beginning of July 1812 — reveals some of the reasons why so many habitants refused to perform their militia duty.
Keywords: Guerre; Lachine; Émeutes

The Empire Within: Montreal, the Sixties, and the Forging of a Radical Imagination - Mills, Sean William (Université Queen's, 2008)
Keywords: Groupes populaires; Idéologies

Democracy, Dissent, and the City: Cross-Cultural Encounters in Sixties Montreal - Mills, Sean (The Sixties in Canada: a Turbulent and Creative Decade, 2009)
Keywords: Femmes; Féminisme; Noirs; Travail

Contester l’empire. Pensée postcoloniale et militantisme politique à Montréal, 1963-1972 - Mills, Sean (Hurtubise, 2011)
Keywords: Groupes populaires; Idéologies